(untitled) (Research, Society and Development, 2022)
The competition between the economically important crop and weeds is a limitation to maximize crop yields, so the association is a technique that seeks to minimize the development of weeds while being friendly to the environment. The objective of this research was to evaluate the decrease in the occurrence of weeds in corn crops associated with Urochloa ruziziensis. The treatment design used was Factorial (2x2) arranged in a completely random design, being factor A Cultivars and factor B Association with Urochloa ruziziensis, with 4 treatments and 6 repetitions totaling 24 experimental units (EU). The determinations evaluated were Green mass of weeds at 30, 50 and 70 days after sowing maize (Mg Ha-1), Length (cm) and diameter (mm) of cob and yield of maize (Mg Ha-1). The data obtained from the experimental plot and for each treatment were statistically evaluated, for this purpose the analysis of variance was used (Test F 5%), which yielded the following conclusions: the competition that occurs between corn and weeds for nutrients, availability of water and photosynthesis during the vegetative and reproductive growth of maize considerably influenced the increase in its productivity, as well as in the parameters of length and diameter of the cob.